An agent-based simulation study for exploring organisation design under environmental uncertainty. (1st January 2013) - Wang, Huanhuan; Hu, Bin; Li, Hu
This study discusses the relationships between Chinese environment and project-based organisation (PBO) based on the perspective of contextuality of organisation design. Firstly the background of organisations in the construction engineering consultancy area (EC-PBO) is introduced and factors that affect their performance are analysed. Then a simulation model is proposed based on the NK model and the complementarity framework. This proposed simulation model can quantify the contextuality and special environmental factors. And an agent-based simulation system is developed. Based on the simulation experiments, coherent complements to the conventional wisdoms are made for organisation design under Chinese environmental conditions. Finally our proposed simulation model is verified through empirical research.